The Role of Natural Support Systems in the Post‐deployment Adjustment of Active Duty Military Personnel. Issue 1 (7th July 2015) - Welsh, Janet A.; Olson, Jonathan; Perkins, Daniel F.; Travis, Wendy J.; Ormsby, LaJuana
Abstract: This study examined the relations among three different types of naturally occurring social support (from romantic partners, friends and neighbors, and unit leaders) and three indices of service member well‐being (self reports of depressive symptoms, satisfaction with military life, and perceptions of unit readiness) for service members who did and did not report negative experiences associated with military deployment. Data were drawn from the 2011 Community Assessment completed anonymously by more than 63, 000 USAF personnel. Regression analyses revealed that higher levels of social support was associated with better outcomes regardless of negative deployment experiences. Evidence of moderation was also noted, with all forms of social support moderating the impact of negative deployment experiences on depressive symptoms and support from unit leaders moderating the impact of negative deployment experience on satisfaction with military life. No moderation was found for perceptions of unit readiness. Subgroup analyses revealed slightly different patterns for male and female service members, with support providing fewer moderation effects for women. These findings may have value for military leaders and mental health professionals working to harness the power of naturally occurring relationships to maximize the positive adjustment of service members and their families. Implications for practices related to re‐integration of post‐deployment military personnel are discussed.